Glorious, accursed Europe : an essay on Jewish ambivalence - Shaviṭ, Yaʻaḳov, 1944- (Tauber Institute for the Study of European Jewry series., 2010)
An exhaustive study of how Jews imagined the idea of Europe and how it existed in their collective memory from the Enlightenment to the present.